2022
DOI: 10.1038/s44172-022-00002-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic spectrum sharing between active and passive users above 100 GHz

Abstract: Sixth-generation wireless networks will aggregate higher-than-ever mobile traffic into ultra-high capacity backhaul links, which could be deployed on the largely untapped spectrum above 100 GHz. Current regulations however prevent the allocation of large contiguous bands for communications at these frequencies, since several narrow bands are reserved to protect passive sensing services. These include radio astronomy and Earth exploration satellites using sensors that suffer from harmful interference from activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The near-field regime in 6G and 7G scenarios is challenged further by the fact that the (sub-)THz spectrum is unlikely to offer continuous bands of many hundreds of GHz, as many sub-bands in sub-THz frequencies (up to 275 GHz) are already occupied by essential services, such as radars, sensors, and Earth satellites (Polese et al, 2022). To stay within reasonable bandwidths (realistically, tens of GHz) while achieving the expected rate of Tbps (Huang and Wang, 2011), spatially multiplexed channels (Akyildiz and Jornet, 2016) are necessary.…”
Section: Challenge 7: Achieving Spatially Multiplexed Channels For Mo...mentioning
confidence: 99%
“…The near-field regime in 6G and 7G scenarios is challenged further by the fact that the (sub-)THz spectrum is unlikely to offer continuous bands of many hundreds of GHz, as many sub-bands in sub-THz frequencies (up to 275 GHz) are already occupied by essential services, such as radars, sensors, and Earth satellites (Polese et al, 2022). To stay within reasonable bandwidths (realistically, tens of GHz) while achieving the expected rate of Tbps (Huang and Wang, 2011), spatially multiplexed channels (Akyildiz and Jornet, 2016) are necessary.…”
Section: Challenge 7: Achieving Spatially Multiplexed Channels For Mo...mentioning
confidence: 99%
“…Going higher in frequency to mmWave and sub-THz spectrum, Xing and Rappaport [27] model potential interference between terrestrial and satellite-based systems operating over 100 GHz, followed by Kumar and Arnon [28] delivering an upper bound on ground-to-satellite channel capacity in Wband (100 GHz-110 GHz). Recently, dynamic spectrum sharing among terrestrial and satellite-based sub-THz wireless systems was experimentally demonstrated by Polese et al [29]. While many of the analytical models discussed above consider a single satellite, there have been several studies explicitly capturing the interference produced by a group of satellites, including but not limited to [30], [31], and [32].…”
Section: A Related Workmentioning
confidence: 99%
“…A third consideration for applications will be the available bandwidth in sub-THz frequencies due to contention with passive satellite use [9] [10]; in essence a contiguous bandwidth limit of 12.5GHz above 100 GHz that will prevent the goal 6G speeds of 1Tbps from being achieved with a single contiguous band. It may be possible with regulatory changes to alter this restriction (such as using dynamic bandwidth allocation [9]), or other techniques like carrier aggregation, but without some action, this limit may impair the full range of sub-THz outdoor fixed wireless service, or some applications that may demand extraordinarily high data rates.…”
Section: The Landscapementioning
confidence: 99%